Implications for welfare, productivity and sustainability of the variation in reported levels of mortality for laying hen flocks kept in different housing systems: A meta-analysis of ten studies - Weeks, Clare A.; Lambton, Sarah L.; Williams, Adrian G. (Public Library of Science (PLoS), 2016)
Data from ten sources comprising 3,851 flocks were modelled to identify variation in levels of mortality in laying hens. The predicted increase with age was curvilinear with significant variation between the seven breed categories. Mortality was higher in loose housing systems than in cages and variable within system, confirming previous reports. Cumulative mortality (CM) was higher in flocks with intact beaks (χ2 = 6.03; df 1; p = 0.014) than in those with trimmed beaks. Most data were available for free-range systems (2,823 flocks), where producer recorded CM at 60–80 weeks of age averaged 10% but with a range from 0% to 69.3%. Life cycle assessment showed that the main effect of increased levels of hen mortality is to increase the relative contribution of breeding overheads, so increasing environmental burdens per unit of production. Reducing CM to levels currently achieved by the 1st quartile could reduce flock greenhouse gas emissions by as much as 25%. Concurrently this would enhance hen welfare and better meet the expectation of egg consumers. More research to understand the genetic x environment interaction and detailed records of the causes of mortality is required so that improved genotypes can be developed for different systems and different breeds can be better managed within systems.